FRI0159 EROSIVE ARTHRITIS IN SYSTEMIC LUPUS ERYTHEMATOSUS: APPLICATION OF CLUSTER ANALYSIS. (2nd June 2020) - Ceccarelli, F.; Natalucci, F.; Perricone, C.; Cipriano, E.; Pirone, C.; Olivieri, G.; Colasanti, T.; Spinelli, F. R.; Alessandri, C.; Valesini, G.; Conti, F.
Abstract : Background: Systemic Lupus Erythematosus (SLE) related arthritis has been traditionally defined non-erosive and then considered a minor manifestation. Thanks to the application of more sensitive imaging techniques, such as ultrasonography (US), erosive damage has been identified in up to 40% of SLE patients with joint involvement, suggesting the need for more appropriate treatment (1). Antibodies directed against citrullinated and carbamilated proteins (ACPA and anti-CarP, respectively) have been associated with erosive damage and then proposed as biomarkers for this more aggressive phenotype (2). Objectives: Here, we evaluated a large SLE cohort with joint involvement by using cluster analysis, in order to identify the disease phenotype associated with erosive arthritis. Methods: For this analysis, we enrolled consecutive SLE patients (ACR 1997 criteria) with a clinical history of joint involvement (arthritis/arthralgia). Clinical and laboratory data were collected in a standardized computerized electronically filled form, including demographics, past medical history with the date of diagnosis, co-morbidities, previous and concomitant treatments, serological status. The presence of rheumatoid factor (RF), ACPA and anti-CarP was investigated by ELISA test. Erosive damage was assessed by ultrasonography at level of metacarpophalangeal, proximal interphalangeal and metatarsophalangeal joints (MyLab Eight Exp, Esaote, Florence, Italy). Data have been analysed by hierarchic cluster analysis (SPSS program, IBM). Results: We enrolled 203 patients [M/F 12/191, median age 46.0 years (IQR 18); median disease duration 120.0 months (IQR 108)]. Erosive damage was identified in 53 patients (26.1%), all of them referring at least one episode of arthritis during disease course. Moving on autoantibodies status, RF was positive in 29.5%, anti-CarP in 28.5% and ACPA in 11.2%. The univariate analysis demonstrated a significant association between US-detected erosive damage and anti-CarP (p=0.01), ACPA (p=0.03), and renal manifestations (p=0.03). In Figure 1 we reported the dendrogram obtained from cluster analysis, allowing the identification of four cluster. Positivity for ACPA, anti-CarP, erosive damage, Jaccoud's arthropathy and renal manifestations were allocated in the same cluster. Interestingly, RF resulted allocated in a different cluster, including ENA, anti-SSA and anti-SSB antibodies. Conclusion: The application of cluster analysis allowed the identification of a specific SLE phenotype, characterized by erosive damage, renal manifestations and positivity for anti-CarP and ACPA. We could speculate about the presence of a shared pathogenic mechanism, involving NETosis, contributing to nephritis and erosive arthritis. References: [1]Ceccarelli F et al. Semin Arthritis Rheum 2017 [2]Ceccarelli F et al. Arthritis Res Ther 2018 Disclosure of Interests: Fulvia Ceccarelli: None declared, Francesco Natalucci: None declared, Carlo Perricone: None declared, enrica cipriano: None declared, Carmelo Pirone: None declared, Giulio Olivieri: None declared, Tania Colasanti: None declared, Francesca Romana Spinelli Grant/research support from: Pfizer, Consultant of: Novartis, Gilead, Lilly, Sanofi, Celgene, Speakers bureau: Lilly, cristiano alessandri Grant/research support from: Pfizer, Guido Valesini: None declared, fabrizio conti Speakers bureau: BMS, Lilly, Abbvie, Pfizer, Sanofi